Research ofwintergarlic storage depending on the elements of the post-harvest refinement - Pusik, Ludmila; Pusik, Vlаdimir; Postnova, Olga; Safronska, Iryna; Chervonyi, Vitalii; Mohutova, Valentyna; Kaluzhnij, Aleksandr (Technology audit and production reserves, 2019)
The object of research is the effect of post-harvest treatment with biological products on the safety of winter garlic. One of the most problematic places is to increase the shelf life of winter garlic for food and at the same time reduce disease damage. Processing of products with biological preparations before laying them in storage, the active strains of which are able to suppress the development of plant diseases, reduce production losses during storage. During the study, varieties of Merefiansky white and Merefiansky pinkwinter garlic grown in the forest-steppe of Ukraine are used. The preparations Gliokladin and Phytosporin are used at a concentration of 2% during the growing season and before being stored. Natural losses, the number of sprouted bulbs of garlic and affected by microbiological diseases, the total losses and the yield of standard products are determined. Processing vegetable products with biological products of various actions helps to extend the shelf life and increase the yield of standard products at the end of storage. It was found that treatment with biological products reduces the incidence of garlic diseases. After 6 months of storage, the untreated bulbs defy themselves with diseases of 8.33–8.93 %. Treatment with Phytosporin reduces the damage to microorganisms to 6.28–6.88 %. The most effective is the treatment of bulbs with Glyocladine. The number of affected bulbs decreases to 2.67–2.69 %. Biological treatment most suppresses the development of fusarium and bacteriosis. The number of affected bulbs is 0.2–0.65 and 1.1–1.6 %, respectively. The safety of winter garlic has a strong direct relationship with weight loss, the number of people affected by diseases and the amount of sprouted bulbs. The processing of garlic by biological preparations for storage does not ensure complete elimination of the harmful species, but only reduces the harmfulness of microorganisms to an acceptable level. The proposed method for processing garlic bulbs with biological products before storage will reduce losses and extend the period of consumption. In the development of new, low-cost, environmentally friendly and affordable storage technologies, this is an important technique.